2014
DOI: 10.1002/app.40539
|View full text |Cite
|
Sign up to set email alerts
|

Pullulan‐based films and coatings for food packaging: Present applications, emerging opportunities, and future challenges

Abstract: Societal and industrial demands for lower environmental impact, cost effectiveness, and high-performance goods and services are increasingly impacting the choice of technologies which are developed and deployed in consumer products. Like many other sectors, food packaging is moving to new technologies; the use of biopolymers is one of the most promising strategies toward an optimized use of traditional packaging materials (e.g., oil-based plastics) without impairing the goal of extending shelf life. Among othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
62
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 161 publications
(67 citation statements)
references
References 90 publications
(105 reference statements)
2
62
0
Order By: Relevance
“…Among the wide assortment of biopolymers, pullulan, an exopolysaccharide produced by the fungus-like yeast Aureobasidium pullulans, is increasingly regarded as a suitable candidate for the fabrication of bionanocomposites due to its unique properties (Farris et al 2014). Pullulan is nontoxic, tasteless, odorless and biodegradable, with high film-forming abilities (Yuen 1974;Trovatti et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Among the wide assortment of biopolymers, pullulan, an exopolysaccharide produced by the fungus-like yeast Aureobasidium pullulans, is increasingly regarded as a suitable candidate for the fabrication of bionanocomposites due to its unique properties (Farris et al 2014). Pullulan is nontoxic, tasteless, odorless and biodegradable, with high film-forming abilities (Yuen 1974;Trovatti et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Diab and others () reported that pullulan coating is capable of accelerating ripening process of kiwifruits, and further altering the self‐life of strawberries. Moreover, the coating film made of pullulan with excellent antifog properties displayed better performances in comparison to another 2 commercial antifog films (Farris and others ). However, pullulan film has inherent disadvantages, such as brittleness, difficult to process by conventional melt processing techniques, and poor water resistance (Farris and others ).…”
Section: Introductionmentioning
confidence: 85%
“…It has been reported that pullulan films exhibit good oxygen barrier properties in low relative humidity conditions, which accounts for the high effectiveness of pullulan film in preventing oxidation and rancidity (Farris and others ). The utilization of pullulan‐based film as coating materials in food preservation has been investigated (Introzzi and others ; Farris and others , ). However, compare pullulan with other natural alternatives (that is, polylactic acid, polycaprolactone, and agar), the studies are rare.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we decided to use the NBB mica in combination with the exopolysaccharide pullulan to develop high-performance oxygen barrier materials that concurrently exhibit outstanding optical, surface, and mechanical properties. Among the variety of biopolymers, Pullulan was selected due to its unique properties, such as high flexibility, excellent transparency, good oxygen barrier properties, and non-toxicity, all of which make it a promising candidate for a next-generation of materials that are totally or partially based on renewable resources [13]. PET has been used as a plastic substrate because of its widespread use in many different applications ranging from food packaging (e.g., liquids containers, thermoforming applications, layers for flexible packaging solutions) to energy applications (e.g., solar cells), displays, and medical/biomedical uses.…”
Section: Introductionmentioning
confidence: 99%